Pengembangan Lembar Kerja Peserta Didik (LKPD) dengan Pendekatan Saintifik untuk Meningkatkan Keterampilan Menulis pada Pembelajaran Bahasa Indonesia di Kelas V (Lima) Sekolah Dasar - Fathonah Putri, Nuraini; Muktadir, Abdul; Widi Winarni, Endang (UNIB Press, 2025)
This research and development develops LKPD with a scientific approach to Indonesian learning. This research and development aims to find out how the development, feasibility, response of teachers and students as well as the effectiveness of Student Worksheets (LKPD) with a scientific approach to Indonesian learning in Grade 5 of State Elementary School 16 Bengkulu City. The method used is the Research and Development method (research and development) using the ADDIE model. The subject of the study was class V.C and V.D students and the object of research was an LKPD product with a scientific approach to Indonesian learning. The research instruments used were needs analysis, interviews, questionnaires, and rubrics on the skills of writing explanatory text summaries. The results showed that the developed LKPD met the logical and empirical feasibility and was qualified for use in learning. This is based on the results of 90% material validation, 82% language validation and 80% design validation. For the response of students, they showed a positive response to the LKPD developed. As well as being quite effective for improving writing skills in Indonesian learning, this can be seen from the results of the significance value (2-tailed) on non-parametric statistical tests, namely 0.000 and the N-Gain Score value of 58.24%. The value shown in the experimental class is higher than that in the control class. Thus, it can be concluded that LKPD with a scientific approach to learning Indonesian is quite effectively used to improve writing skills in Indonesian learning in Grade V (five) Elementary School.